2009
DOI: 10.1093/humrep/dep212
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene Glu298Asp polymorphism is associated with advanced stage endometriosis

Abstract: These findings suggest that the T allele, encoding aspartic acid, of the Glu298Asp polymorphism of the NOS3 may be associated with advanced stage endometriosis in the Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Furthermore, studies of single nucleotide polymorphism s reveal that GSTT1 (glutathione-S-transferase) null deletion [36] and eNOS [20] are associated with moderate risk of endometriosis. In addition, endometriosis-related infertility is associated with glutathione peroxidase activity [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies of single nucleotide polymorphism s reveal that GSTT1 (glutathione-S-transferase) null deletion [36] and eNOS [20] are associated with moderate risk of endometriosis. In addition, endometriosis-related infertility is associated with glutathione peroxidase activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high levels of serum and follicular NO in patients with endometriosis were associated with poor embryo quality and pregnancy outcome in assisted reproduction technology cycles [22]. Other previous studies have indentified the association of a polymorphism of endothelial NOS with advanced stage endometriosis [20]. Overall, increased microenviromental NO (in follicular fluid, tubal secretions, and endometrial tissue) might contribute to the pathologic effects of endometriosis on the development potential of embryos.…”
Section: Introductionmentioning
confidence: 89%
“…NOS3 may modulate angiogenesis and influence individual susceptibility to endometriosis, and it is widely accepted that angiogenesis plays an essential role in the growth and survival of endometriotic lesions. Moreover, NOS3 has also been reported to be associated with advanced stage endometriosis in a Korean population [33, 34]. Previous studies have shown altered levels of the CALD1 gene (encoding the protein caldesmon) in endometriosis and that precursor protein of caldesmon is a possible predictor of endometrial dysregulation in patients with endometriosis [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy of prematurity is associated with all three polymorphisms (Rusai et al 2008;Yanamandra et al 2010), whereas the coding polymorphism affects endometriosis (Kim et al 2009a), and the promoter polymorphism affects idiopathic osteonecrosis of the femoral head (Glueck et al 2007).…”
Section: Nitric Oxide Synthase (Nos3/enos)mentioning
confidence: 99%